The Effectiveness of the Project-Based Learning Model in Learning Writing Skills for Fiction Review Texts - Shafa Arwen; Nursaid; Andria Catri Tamsin; Vivi Indriyani (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
This study tested the effectiveness of the Project Based Learning (PjBL) model in teaching writing fiction review texts. This study took place in the even semester of the 2025/2026 academic year using a quasi-experimental pre-test post-test single group design in class XI SMKN 3 Padang. The population of this study were students of class XI TKJ 2 who participated in learning activities to write fiction reviews before using the PjBL model and who participated in learning to write fiction reviews after using the PjBL model and submitted fiction review writing tests in each learning activity. They numbered 34 students. The sample was determined to be 32 students based on a statistical formula developed by Slavin. Data on writing fiction reviews were collected using a test for work on one of two short story texts provided. The test was compiled using a systematic and objective procedure using eleven indicators. The answer sheet was scored using a scoring rubric involving eleven indicators containing 80 maximum scores and 0 minimum scores. A checklist was used to internally validate the scoring results and the results of the data analysis. The research data were analyzed using parametric inferential statistical procedures, namely a one-sample t-test for each test result and a paired sample t-test to determine the effectiveness of the PjBL model in learning to write reviews of fictional works. The results of the study: 1) the results of learning to write fictional work review texts before using the PjBL model were in the low category; 2) the results of learning to write fictional work review texts after using the PjBL model were in the high category; 3) the PjBL model was effective for use in learning to write fictional work reviews in class XI of SMKN 3 Padang.